Impulsivity in patients with borderline personality disorder: a comprehensive profile compared with healthy people and patients with ADHD - Linhartová, Pavla; Látalová, Adéla; Barteček, Richard; Širůček, Jan; Theiner, Pavel; Ejova, Anastasia; Hlavatá, Pavlína; Kóša, Barbora; Jeřábková, Barbora; Bareš, Martin; Kašpárek, Tomáš (Psychological medicine, 2020)
BACKGROUND: Impulsivity is a core symptom of borderline personality disorder (BPD). Impulsivity is a heterogeneous concept, and a comprehensive evaluation of impulsivity dimensions is lacking in the literature. Moreover, it is unclear whether BPD patients manifest impaired cognitive functioning that might be associated with impulsivity in another patient group, such as ADHD, a frequent comorbidity of BPD. METHODS: We tested 39 patients with BPD without major psychiatric comorbidities and ADHD, 25 patients with ADHD, and 55 healthy controls (HC) using a test battery consisting of a self-report measure of impulsivity (UPPS-P questionnaire), behavioral measures of impulsivity - impulsive action (Go/NoGo task, stop signal task) and impulsive choice (delay discounting task, Iowa gambling task), and standardized measures of attention (d2 test), working memory (digit span), and executive functioning (Tower of London). RESULTS: Patients with BPD and ADHD, as compared with HC, manifested increased self-reported impulsivity except sensation seeking and increased impulsive choice; patients with ADHD but not BPD showed increased impulsive action and deficits in cognitive functioning. Negative urgency was increased in BPD as compared to both HC and ADHD groups and correlated with BPD severity. CONCLUSIONS: Patients with BPD without ADHD comorbidity had increased self-reported impulsivity and impulsive choice, but intact impulsive action and cognitive functioning. Controlling for ADHD comorbidity in BPD samples is necessary. Negative urgency is the most diagnostically specific impulsivity dimension in BPD.
Keywords: dospělí; Attention Deficit Disorder with Hyperactivity; impulsivity; krátkodobá paměť; hraniční porucha osobnosti; studie případů a kontrol; Self Report; Impulsive Behavior; Executive Function; Humans; rozhodování; working memory.; zpráva o sobě; ADHD; attention; mladý dospělý; impulzivní chování; Czech Republic; kognice; mužské pohlaví; executive functions; Česká republika; borderline personality disorder; exekutivní funkce; Adult; Adolescent; hyperkinetická porucha; Borderline Personality Disorder; urgency; ženské pohlaví; cognitive functions; decision making; Memory, Short-Term; Cognition; Decision Making; lidé; Case-Control Studies; mladiství; Male; Young Adult; Female